2010
DOI: 10.1111/j.1750-3841.2010.01907.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oryzanol and Ferulic Acid on the Glucose Metabolism of Mice Fed with a High‐Fat Diet

Abstract: The effects of oryzanol and ferulic acid on the glucose metabolism of high-fat-fed mice were investigated. Male C57BL/6N mice were randomly divided into 4 groups: NC group fed with normal control diet; HF group fed with high-fat (17%) diet; HF-O group fed with high-fat diet supplemented with 0.5% oryzanol; and HF-FA group fed with high-fat diet supplemented with 0.5% ferulic acid. All animals were allowed free access to the experimental diets and water for 7 wk. At the end of the experimental period, the HF-O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 32 publications
6
95
1
2
Order By: Relevance
“…OZ supplementation (100 mg/kg/day, p.o.) significantly restored the Na + -K + ATPase activity, possibly by attenuation of oxidative stress (Son et al, 2011) and amelioration of vascular function (Kihara et al, 1991).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…OZ supplementation (100 mg/kg/day, p.o.) significantly restored the Na + -K + ATPase activity, possibly by attenuation of oxidative stress (Son et al, 2011) and amelioration of vascular function (Kihara et al, 1991).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, although previously conducted research has established the hypoglycemic potential of OZ by virtue of its regulation of adiponectin and insulin secretion and hepatic glucose-regulating enzyme activities (Ohara et al, 2009;Son et al, 2011), the physiological role of OZ in relation to chronic diabetic complications in experimental animal models is not fully established and requires extensive research. Therefore, the present study was designed to investigate the effect of OZ, a potent free radical scavenger, on nociception and oxidative stress in STZ-induced DN model in rats.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies ( Table 2) have revealed a reduction in inflammatory markers and oxidative stress, a decrease in body weight and improvements in carbohydrate and lipid metabolism by phenolic acid activity [78][79][80][81][82][83][84][85]. For example, hydroxycinnamic acids and their derivatives may regulate adiponectin secretion by inhibiting NF-kB and leukotriene formation [78], but they may also have anti-oxidant and antiglycation properties [86].…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…For example, hydroxycinnamic acids and their derivatives may regulate adiponectin secretion by inhibiting NF-kB and leukotriene formation [78], but they may also have anti-oxidant and antiglycation properties [86]. Ferulic acid and its derivative, gamma-oryzanol, reduced the risk of high-fat diet-induced hyperglycemia via regulation of insulin secretion and hepatic glucose-regulating enzyme activities [81]. A recent review has shown that ferulic acid derivatives may mediate antiinflammatory effects by down-regulating the proinflammatory transcription factor NF-κB, which in turn can reduce the expression of inflammatory enzymes, such as COX-2 and iNOS, and pro-inflammatory cytokines, such as IL-1β, IL-6 and TNF-α.…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Ferulic acid has been shown to promote weight loss in rats and improve serum glucose levels in mice fed a high-fat diet. 19,20) Intake of kaempferol ameliorates hyperglycemia, hyperinsulinemia and circulating lipid profile, which are associated with improved peripheral insulin sensitivity in mice fed a high-fat diet. 21,22) Upregulation of carnitine palmitoyltransferase 1 by p-coumaric acid improves liver fat metabolism.…”
Section: )mentioning
confidence: 99%